2021
DOI: 10.1021/acsnano.1c06595
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Raman Characterization of a 2D Semiconductor Lateral Heterostructure Interface

Abstract: The nature of the interface in lateral heterostructures of 2D monolayer semiconductors including its composition, size, and heterogeneity critically impacts the functionalities it engenders on the 2D system for next-generation optoelectronics. Here, we use tipenhanced Raman scattering (TERS) to characterize the interface in a single-layer MoS 2 /WS 2 lateral heterostructure with a spatial resolution of 50 nm. Resonant and nonresonant TERS spectroscopies reveal that the interface is alloyed with a size that var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…Before we come to the conclusions, it is necessary to note that 638 nm excitation is not necessarily the one providing a spectrally deficient TERS response, the completeness of the TERS spectra depends on matching the excitations to the resonant absorption profile of corresponding sample. For example, in recent work on the TERS characterization of the MoS 2 −WS 2 lateral heteromonolayers, Garg et al showed 28 that the TERS spectra of the alloyed Mo x W (1−x) S 2 heterojunction collected with 638 nm excitation featured strong Raman bands in the 210 to 220 cm −1 range, which were completely absent in the TERS spectra of the same alloyed junction area collected with 785 nm excitation, which is significantly below the optical band gap for both MoS 2 and WS 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Before we come to the conclusions, it is necessary to note that 638 nm excitation is not necessarily the one providing a spectrally deficient TERS response, the completeness of the TERS spectra depends on matching the excitations to the resonant absorption profile of corresponding sample. For example, in recent work on the TERS characterization of the MoS 2 −WS 2 lateral heteromonolayers, Garg et al showed 28 that the TERS spectra of the alloyed Mo x W (1−x) S 2 heterojunction collected with 638 nm excitation featured strong Raman bands in the 210 to 220 cm −1 range, which were completely absent in the TERS spectra of the same alloyed junction area collected with 785 nm excitation, which is significantly below the optical band gap for both MoS 2 and WS 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…From the bottom-up, material stoichiometry can be tailored through the introduction of defects, ,, interfaces in lateral heterostructures, or alloying, , providing additional opportunities to tune electronic structure and optoelectronic phenomena. For localized bottom-up engineering, interfaces play a central role, and the functionality that they engender in a lateral 2D heterostructure is intricately intertwined with that of alloys as the size of the transition between pristine materials can range from atomically sharp to hundreds of nanometers. , …”
Section: Introductionmentioning
confidence: 99%
“…The potential of tailored properties at alloyed interfaces has been demonstrated by state-of-the-art computational and experimental studies of how the exchange of metal or chalcogen atoms alters the properties of the material, complementing layer- and thickness-dependent properties in stacked heterostructures . Computational and experimental studies of alloyed systems have been performed for Mo x W 1– x S 2 , ,, Mo x W 1– x Te 2 , MoS 2 x Se 2(1– x ) , Mo 1– x W x Te 2 , and MoTe x Se 2– x , among others . A shared focal point of the past computational studies has been to predict the macroscopic properties of the 1L alloys.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations